The Impact of Organization Costs when Firm-selection Matters - Jörg Lingens; Marco De Pinto; Christian Bauer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
How does an increase in organization costs (i.e. costs which arise when labor unions organize firm's workforces) affect the industry struc-ture, wage inequality and welfare? In the present paper, we build a model with costly and endogenous unionization, heterogeneous firms as well as free market entry/exit. In such a setting, we show that the share of low-productive firms operating in the market decreases (in-creases) in organization costs if those costs are relatively low (high). If more low-productive firms are active in the market, consumption and hence welfare decline because prices are, on average, higher (vice versa). As such, an increase in organization costs and thus a decline in unionization rates could be welfare-reducing. In addition, we find a hump-shaped relationship between organization costs and wage in-equality. These results suggest that a policy aiming to reduce union-ization by an increase in organization costs can but not necessarily have to be an improvement of the economic performance.
Keywords: J51; L11; L16; 330